I tofet e i santuari di Saturno nell'Africa di età romana: localizzazione, rapporto spaziale e caratteristiche tipologiche e cultuali - (:unkn) unknown (My University, 2017)
The purpose of the present paper is to examine the relationships between the Tophets, which are Phoenicians and Carthaginians sanctuaries dedicated to Baal Hammon and Tinnit, and the temples dedicated to Saturn, which are in religious continuity with the Tophets, from the 2nd century BC to the 2nd century AD. In this period, Carthage loss her possessions in North Africa and Rome, with the destruction of Carthage in 146 BC, gradually conquests and organizes administratively the North-African regions. The paper analyses the geographical location of these sanctuaries, their spatial relationships and their typological and ritual features through a synchronic and a diachronic dimension in connection with the socio-political and cultural changes that have occurred
Keywords: African Research